STUDI LITERATUR ANALISIS TENTANG DAMPAK YOGA DAN MEDITASI TERHADAP KESEHATAN PADA DEWASA MUDA - Hawari Daulay, Ariq; Safitri, Rina; Salsabila; Gultom, Syamsul; Hotliber Purba , Pangondian (Fakultas Ilmu Keolahragaan Unimed, 2026)
This study aims to analyze the impact of yoga and meditation on mental, emotional, and cognitive health among young adults. The method employed was a systematic literature review of 25 accredited scientific articles published between 2012 and 2025 through stages of data collection, selection, and thematic synthesis. The findings indicate that regular yoga and meditation practices can reduce stress, anxiety, and depression, while enhancing psychological well-being, sleep quality, and cognitive performance. Physiologically, yoga decreases cortisol and increases serotonin levels, whereas meditation enhances self-awareness and emotional regulation. Socially, group practices foster empathy and social connectedness. In conclusion, yoga and meditation serve as effective promotive and preventive interventions for maintaining young adults’ mental health and are potentially integrable into educational and community wellness programs.